Comment on "A comparative evaluation of the narrative thoughts in Chinese and Western classical literature" - Wei, Gaixia (2024)
Commented article: CHEN, M. A comparative evaluation of the narrative thoughts in Chinese and Western classical literature. Trans/Form/Ação: Unesp journal of philosophy, v. 47, n. 5, e02400135, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/15070.